Globalization and developing countries - a shrinking tax base? - Joshua Aizenman; Yothin Jinjarak (University of California, Santa Cruz Institute for International Economics (SCIIE), 2006)
This paper evaluates the impact of globalization on the tax bases of countries at varying stages of development. We see globalization as a process that induces countries to embrace greater trade and financial integration, and macro stabilization. This in turn should shift their tax base from easy to collect taxes [tariff, seigniorage, etc.] towards hard to collect taxes [VAT, income tax, etc.]. We confirm this prediction the revenue/GDP ratio of the easy to collect taxes declined by about 12% in developing countries between the early 1980s and the late 1990s, while the revenue/GDP of the hard to collect taxes increased by 16%. The relatively small initial base of hard to collect taxes in developing countries implied a net 2% drop in total tax revenue/GDP. Applying panel regressions and controlling for structural factors, we find that trade openness and financial integration have a positive relationship with hard to collect taxes, and negative relationship with the easy to collect taxes. Fiscal revenue from financial repression has also decreased, further reinforcing these results. The high income and the middle income countries managed to more than compensate for the revenue decline of the easy to collect taxes, increasing the total tax/GDP. In contrast, the upper and low income developing countries experienced sizeable drop in the tax/GDP. We also identify strong fiscal convergence during 1980s - 1990s: the coefficient of variation of tax revenue/GDP measures across countries declined by about 40% for seigniorage, about 40% for tariff, and about 4% for the hard to collect taxes. We confirm the robustness of the main results to IV methodology, where trade globalization is inferred from applying the gravity methodology. These results are consistent with the notion that improving the performance of the hard to collect taxes is more challenging than reducing the use of easy to collect sources of revenue.
Keywords: F15; H21; 330; globalization; tax base; fiscal convergence; VAT; financial repression; tariff; Globalisierung; Steueraufkommen; Steuerbemessung; Indirekte Steuer; Direkte Steuer; Vergleich; Entwicklungsländer